Предмет: Математика, автор: sayathshahsis

Помогите пожалуйста номер 627

Приложения:

Ответы

Автор ответа: sangers1959
1

Пошаговое объяснение:

627.

1)\ (-\frac{3}{7}*\frac{1}{4})*(-4)=-\frac{3*1*(-4)}{7*4} =\frac{3}{7} .\\2)\  (-4\frac{1}{5} *1,3)*\frac{10}{13} =-4\frac{1}{5}  *\frac{13}{10}*\frac{10}{13}=-4\frac{1}{5}.\\3)\   (-5\frac{6}{7} *\frac{3}{13})*(-4\frac{1}{3})=-5\frac{6}{7}*\frac{3}{13} *(-\frac{13}{3})=5\frac{6}{7}.\\4)\ -(7\frac{5}{12} *\frac{7}{36})*5\frac{1}{7} =-7\frac{5}{12}  *\frac{7}{36} *\frac{36}{7}=-7\frac{5}{12}.


sayathshahsis: Спасибо
sangers1959: Удачи.
Похожие вопросы
Предмет: Алгебра, автор: Nic122